Pre-coated steel sheet

By adjusting the distribution state of zirconium on the galvanized steel plate of the pre-coated metal plate and adding resin particles, the problems of damage resistance and adhesion reduction caused by thickening of the coating film are solved, and better performance is achieved.

CN119923319APending Publication Date: 2025-05-02NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380068285.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-27
Filing Date
2023-09-27
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When the coating film thickness is thickened, damage resistance and film adhesion are easily reduced.

Method used

The galvanized steel plate is used as the base material, and the distribution state of zirconium is adjusted at the interface between the Zn-containing coating layer and the coating film, and resin particles are added to the coating film to ensure the damage resistance and adhesion of the coating film.

Benefits of technology

Even when the coating film is thicker, it is possible to achieve better damage resistance and coating film adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923319A_ABST
    Figure CN119923319A_ABST
Patent Text Reader

Abstract

In order to achieve more excellent scratch resistance and coating film adhesion even when a coating film is thick, this precoated steel sheet is provided with: a Zn-containing plating layer; a chemical conversion coating layer containing at least zirconium; and a coating layer containing at least a binder resin and resin particles, the average thickness of the coating layer being 3 [mu] m or more and 10 [mu] m or less, wherein: the strength of zirconium at the interface on the Zn-containing plating layer side of the coating layer calculated from a depth curve relating to the zirconium distribution of the coating layer obtained by glow discharge emission spectrometry is 1.05-3.00 times (inclusive) of the average strength of zirconium in the range of 1-2 [mu] m (inclusive) from the surface of the coating layer; in a region having a length of 60 [mu] m in a direction orthogonal to the thickness direction, when a cross-section obtained by cutting the coating layer in the thickness direction is observed, the average area ratio occupied by the resin particles in the region is 5%-30% (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to pre-coated steel sheets. Background Art

[0002] Organic resin coated plated steel sheets (also called pre-coated steel sheets) in which the surface of galvanized steel sheets is coated with an organic resin film have replaced the post-coating products that were previously painted after forming processing, and are used in home appliances, building materials, automobiles, etc. The pre-coated steel sheet is a steel sheet that has been subjected to rust prevention treatment and a plated steel sheet that has been coated with a colored organic film. It has aesthetic appeal, processability, and good corrosion resistance. In many cases, the organic resin coated plated steel sheet can be used as a material for home appliances, building materials, automobiles, etc. without further coating after pressing. Therefore, this organic resin coated plated steel sheet requires excellent damage resistance to avoid losing its beauty during processing. Therefore, in order to improve the various properties of the pre-coated steel sheet, mainly damage resistance, various technologies have been proposed in the past.

[0003] For example, the following patent document 1 discloses a pre-coated metal plate for electronic and electrical equipment that is excellent in not only scratch resistance but also corrosion resistance and conductivity. The pre-coated metal plate is provided with a chemical conversion film on the surface of a metal plate having a predetermined surface roughness, and a resin film having a film thickness of 0.4 to 2.0 μm mixed with polyurethane beads and fluororesin beads having an average particle size of 1 to 10 μm is provided on one surface, and a resin film having a film thickness of 0.2 to 2.0 μm mixed with polyurethane beads and fluororesin beads having an average particle size of 0.1 to 6.0 μm is provided on the other surface.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-5545 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] Here, various pre-coated metal plates including the pre-coated metal plate disclosed in the above-mentioned Patent Document 1 are generally manufactured by providing a desired coating film on a metal plate as a base material (for example, a steel plate including various plated steel plates, an aluminum plate, an aluminum alloy plate, etc.) through a continuous coating line. The metal plate provided with the desired coating film is rolled into a coil at the end of the continuous coating line and then transported to the customer.

[0009] At this time, the film thickness of the formed coating film is generally thin, at most about 2 μm, as disclosed in the above-mentioned Patent Document 1, and the color tone of the metal plate as the base material (for example, the color tone of the plated steel plate used as the base material) can often be seen through. For this reason, when providing pre-coated metal sheets to customers, color design is sometimes performed that also takes into account the base material color tone that can be seen through.

[0010] On the other hand, from the perspective of the color stability of the pre-coated metal sheet provided, it is sometimes preferred that the color of the metal sheet as the base material is not visible through. In order to prevent the color of the metal sheet as the base material from being visible through, it is presumed that the film thickness of the coating film provided on the base material can be increased. However, if the film thickness of the coating film is increased, the damage resistance and coating film adhesion of the pre-coated metal sheet are likely to decrease.

[0011] Therefore, the present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a precoated steel sheet capable of achieving more excellent scratch resistance and coating film adhesion even when the coating film has a thick film thickness.

[0012] Solutions for solving problems

[0013] In order to solve the above problems, the present inventors conducted in-depth research and obtained the following technical concept: when using a galvanized (Zn) steel sheet as a base material, the distribution state of the bonding components at the interface between the Zn-containing coating layer and the coating film is appropriately improved to improve the coating film adhesion, and at the same time, by making the coating film contain resin particles, the damage resistance of the coating film is ensured. Based on this technical concept, the present inventors conducted further research and came up with the present invention described below.

[0014] The gist of the present invention accomplished based on the above findings is as follows.

[0015] (1) A precoated steel sheet comprising: a Zn-containing plating layer located on a surface of a base steel sheet; a chemical conversion coating layer located on the Zn-containing plating layer and containing at least zirconium; and a coating layer located on the chemical conversion coating layer, the coating layer containing at least a binder resin and resin particles, the coating layer having an average thickness of 3 μm or more and 10 μm or less, an intensity of zirconium at an interface on the Zn-containing plating layer side of the coating layer calculated from a depth curve associated with zirconium distribution of the coating layer obtained by glow discharge emission spectroscopy being 1.05 or more and 3.00 or less relative to an average intensity of zirconium in a range of 1 μm or more and 2 μm or less from the surface of the coating layer toward a thickness direction of the coating layer calculated from the depth curve, and when observing a cross section obtained by cutting the coating layer in the thickness direction, in a region having a length of 60 μm in a direction perpendicular to the thickness direction, an average area ratio occupied by the resin particles in the region is 5% or more and 30% or less.

[0016] (2) The precoated steel sheet according to (1), wherein the coating layer further contains at least one of a crosslinking agent and a coloring pigment.

[0017] (3) The precoated steel sheet according to (2), wherein the cross-linking agent is at least one of a melamine resin and an isocyanate resin.

[0018] (4) The precoated steel sheet according to (1) or (2), wherein the resin particles are made of the same type of resin as the binder resin.

[0019] (5) The precoated steel sheet according to (1) or (2), wherein the average particle size of the resin particles is within a range of 1.5 to 15.0 μm.

[0020] (6) A precoated steel sheet according to (1) or (2), wherein the average particle size of the resin particles is in the range of 3.0 to 10.0 μm, the content of the resin particles in the coating layer is 5 to 15% by mass relative to the total content of the binder resin and the resin particles, and the average thickness of the coating layer is in the range of 4 to 8 μm.

[0021] (7) The precoated steel sheet according to (1) or (2), wherein the resin particles are acrylic resin particles.

[0022] Effects of the Invention

[0023] According to the present invention described above, even when the coating film has a thick film thickness, more excellent scratch resistance and coating film adhesion can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1A This is an explanatory diagram schematically showing the structure of a pre-coated steel sheet according to an embodiment of the present invention.

[0025] Figure 1B It is an explanatory diagram schematically showing the structure of the precoated steel sheet according to this embodiment.

[0026] Figure 2 It is an explanatory diagram for explaining the coating layer of the precoated steel sheet according to this embodiment.

[0027] Figure 3 It is an explanatory diagram of the coating layer of the precoated steel sheet according to this embodiment. DETAILED DESCRIPTION

[0028] The preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. It should be noted that in this specification and the drawings, components having substantially the same functional configuration are marked with the same reference numerals to omit repeated descriptions.

[0029] (About pre-coated steel sheets)

[0030] The following references Figure 1A and Figure 1B The precoated steel sheet according to the embodiment of the present invention will be described in detail. Figure 1A and Figure 1B This is an explanatory diagram schematically showing the structure of a precoated steel sheet according to the present embodiment.

[0031] <About the overall structure of pre-coated steel sheets>

[0032] like Figure 1A As schematically shown, the precoated steel sheet 1 of this embodiment includes: a galvanized steel sheet 10 as a base material; a chemical conversion coating layer 20 located on one side of the galvanized steel sheet 10 ; and a coating layer 30 located on the chemical conversion coating layer 20 .

[0033] In addition, if Figure 1A As shown, the galvanized steel sheet 10 as a base material includes a base steel sheet 11 and a Zn-containing plating layer 13 provided on the surface of the base steel sheet 11 .

[0034] It should be noted that if Figure 1B As schematically shown, the chemical conversion coating layer 20 and the coating layer 30 may be provided on both surfaces of the galvanized steel sheet 10 .

[0035] <About galvanized steel sheet 10>

[0036] As described above, the galvanized steel sheet 10 as a base material in the precoated steel sheet 1 of the present embodiment includes the base steel sheet 11 and the Zn-containing plating layer 13 .

[0037] 《Base Steel Plate 11》

[0038] Here, various steel plates such as aluminum-killed steel, ultra-low carbon steel containing Ti, Nb, etc., and high-strength steel containing strengthening elements such as P, Si, and Mn in ultra-low carbon steel can be used as the base steel plate 11 .

[0039] The thickness of the base steel plate 11 may be appropriately set according to the mechanical strength etc. required for the pre-coated steel plate 1, and may be set to about 0.2 mm to 10.0 mm, for example.

[0040] 《Zn-containing coating layer 13》

[0041] The Zn-containing coating layer 13 is located on the surface of the above-mentioned base steel sheet 11. The Zn-containing coating layer 13 is composed of various zinc-based platings. Examples of the zinc-based plating include hot-dip galvanizing, electrogalvanizing, zinc-nickel alloy plating, alloyed hot-dip galvanizing, aluminum-zinc alloy plating, zinc-aluminum-magnesium alloy plating, zinc-vanadium composite plating, and zinc-zirconium composite plating.

[0042] In such zinc-based plating, it is particularly preferred to use zinc-aluminum-magnesium alloy plating as the Zn-containing plating layer 13, and it is more preferred to use zinc-aluminum-magnesium-silicon alloy plating containing Al: 4 to 22 mass%, Mg: 1 to 10 mass%, Si: 0.0001 to 2.0000 mass%, and the remainder being Zn and impurities.

[0043] [Al: 4 to 22 mass %]

[0044] By setting the Al content to 4% by mass or more, the corrosion resistance of the steel plate can be further improved. The Al content is more preferably 5% by mass or more. On the other hand, by setting the Al content to 22% by mass or less, the corrosion resistance of the steel plate can be further improved while suppressing the saturation of the corrosion resistance improvement effect as described above. The Al content is more preferably 16% by mass or less.

[0045] [Mg: 1 to 10 mass %]

[0046] By setting the Mg content to 1% by mass or more, the corrosion resistance of the steel sheet can be further improved. The Mg content is more preferably 2% by mass or more. On the other hand, in the plating bath used for forming the plating layer, by adjusting the Mg concentration so that the Mg content in the Zn-containing plating layer 13 after production is 10% by mass or less, the generation of dross in the plating bath can be stabilized and the plated steel sheet can be stably produced. It is more preferable to adjust the Mg concentration in the plating bath used for forming the Zn-containing plating layer 13 so that the Mg content in the Zn-containing plating layer 13 after production is 5% by mass or less.

[0047] [Si: 0.0001 to 2.0000 mass %]

[0048] By setting the Si content to 0.0001 mass % or more, the adhesion of the Zn-containing plating layer 13 (more specifically, the adhesion between the base steel plate 11 and the Zn-containing plating layer 13) can be further improved. On the other hand, by setting the Si content to 2.0000 mass % or less, the adhesion of the Zn-containing plating layer 13 can be further improved while suppressing the saturation of the adhesion improvement effect of the Zn-containing plating layer 13. The Si content is more preferably 1.6000 mass % or less.

[0049] Furthermore, the Zn-containing plating layer 13 of the present embodiment may contain 1 mass % or less of an element such as Fe, Sb, or Pb alone or in combination to replace a part of the balance Zn.

[0050] Examples of the galvanized steel sheet 10 having a Zn-containing coating layer 13 having the above-mentioned chemical composition include hot-dip galvanized-aluminum-magnesium-silicon alloy steel sheets such as steel sheets having a Zn-11% Al-3% Mg-0.2% Si alloy coating layer (for example, "Super Dima (registered trademark)" manufactured by Nippon Steel Corporation).

[0051] The Zn-containing coating layer 13 as described above can be manufactured, for example, as follows. First, the surface of the prepared base steel plate 11 is subjected to pretreatment such as cleaning and degreasing as required. Then, the base steel plate 11 subjected to the pretreatment is immersed in a hot dip coating bath having a desired chemical composition as required, and the steel plate is pulled from the coating bath. In the coating operation, the coating can be performed by any of a continuous coating method of a coil or a coating method of a single cut plate.

[0052] The temperature of the hot-dip coating bath varies depending on the composition, but is preferably in the range of 400 to 500°C, for example.

[0053] In addition, the coating weight of the Zn-containing coating layer 13 can be controlled by adjusting the pulling speed of the steel sheet, the flow rate and flow rate of the wiping gas ejected from the wiping nozzle disposed above the coating bath, etc. The coating weight is preferably 30 g / m2 in total on both sides of the steel sheet. 2 Above (i.e., 15g / m per side 2 By setting the adhesion amount to 30 g / m 2 As described above, the corrosion resistance of the galvanized steel sheet 10 can be reliably ensured. The coating weight is more preferably 40 g / m2 in total on both sides of the steel sheet. 2 On the other hand, the coating weight is preferably 600 g / m2 on both sides of the steel plate. 2 Below (i.e., 300g / m per side 2 By setting the adhesion amount to 600 g / m 2 The following can further improve the corrosion resistance while ensuring the smoothness of the surface of the Zn-containing plating layer 13. The plating coating weight is more preferably 550 g / m2 in total on both sides of the steel plate. 2 the following.

[0054] After adjusting the amount of hot-dip coating, the steel sheet is cooled. At this time, the cooling conditions do not need to be particularly limited.

[0055] The galvanized steel sheet 10 according to the present embodiment has been described above.

[0056] <About the chemical conversion treatment coating layer 20>

[0057] The chemical conversion coating layer 20 of the present embodiment is a coating layer located between the galvanized steel sheet 10 and the coating layer 30 , and is a layer formed by so-called chemical conversion treatment.

[0058] The chemical conversion coating layer 20 of the present embodiment contains at least a zirconium compound, and may contain any one or more of the group consisting of, for example, resin, silane coupling agent, silicon dioxide, phosphoric acid and its salt, fluoride, vanadium compound, and tannin or tannic acid, as required. That is, it can be said that the chemical conversion coating layer 20 of the present embodiment is a coating layer containing at least zirconium. By containing these substances, the film-forming property after the chemical conversion treatment liquid is applied, the barrier property (compactness) of the coating to corrosion factors such as moisture and corrosive ions, and the adhesion of the coating to the plated surface are improved, which can help improve the corrosion resistance of the coating.

[0059] In particular, since the chemical conversion coating layer 20 contains a zirconium compound (more preferably, also contains a silane coupling agent), a cross-linked structure is formed in the chemical conversion coating layer 20 and the bonding with the plated surface is also strengthened, thereby improving the adhesion and barrier properties of the coating.

[0060] In addition, when the chemical conversion coating layer 20 also contains one or more of silicon dioxide, phosphoric acid and its salts, fluorides or vanadium compounds, these substances function as inhibitors to form a precipitated film or a passivation film on the plating layer or the steel surface, thereby further improving the corrosion resistance.

[0061] The following describes in detail each component that may be included in the chemical conversion coating layer 20 as described above with examples.

[0062] [Zirconium compounds]

[0063] As zirconium compounds, for example, zirconium n-propoxide, zirconium n-butoxide, zirconium tetraacetylacetonate, zirconium monoacetylacetonate, zirconium diacetylacetonate, zirconium monoethyl acetoacetate, zirconium acetylacetonate combined with diethyl acetoacetate, zirconium acetate, zirconium monostearate, zirconium carbonate, ammonium zirconium carbonate, potassium zirconium carbonate, sodium zirconium carbonate, etc. can be cited. The amount of zirconium compound added in the chemical conversion treatment agent used to form the chemical conversion treatment coating layer 20 can be set to 2 to 80 g / L, for example. When the amount of zirconium compound added is less than 2 g / L, the adhesion to the plated surface is insufficient, and there is a possibility that the processing adhesion of the coating is reduced. In addition, when the amount of zirconium compound added exceeds 80 g / L, the cohesion of the chemical conversion treatment coating layer 20 is insufficient, and there is a possibility that the processing adhesion with the coating layer is reduced. The zirconium compound can be used alone or in combination of two or more.

[0064] [Resin]

[0065] The resin is not particularly limited, and for example, well-known organic resins such as polyester resin, polyurethane resin, epoxy resin, phenolic resin, acrylic resin, and polyolefin resin can be used. In order to further improve the adhesion with the plated steel sheet for pre-coated steel sheet, it is preferred to use at least one of the resins (polyester resin, polyurethane resin, epoxy resin, acrylic resin, etc.) having a forced site and a polar functional group in the molecular chain. The resin can be used alone or in combination of two or more.

[0066] The resin content in the chemical conversion coating layer 20 is preferably 0% by mass or more, and more preferably 1% by mass or more, relative to the solid content of the coating. In addition, the resin content in the chemical conversion coating layer 20 is preferably 85% by mass or less, more preferably 60% by mass or less, and further preferably 40% by mass or less, relative to the solid content of the coating. When the resin content exceeds 85% by mass, the proportion of other coating constituent components decreases, and the performance required as a coating other than corrosion resistance may decrease.

[0067] [Silane coupling agent]

[0068] Examples of the silane coupling agent include γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropylmethyldiethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, N-β-( N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltriethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropylmethyldiethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyl γ-Mercaptopropylmethyldimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-mercaptopropylmethyldiethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, vinyltriacetoxysilane, γ-chloropropyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltriethoxysilane, γ-chloropropylmethyldiethoxysilane, hexamethyldisilazane, γ-anilinopropyltrimethoxysilane, γ-anilinopropylmethyldimethoxysilane, γ-anilinopropyltriethoxysilane, γ-anilinopropylmethyldiethoxysilane, Alkenyltrimethoxysilane, vinylmethyldimethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, octadecyldimethyl[3-(trimethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(methyldimethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(triethoxysilyl)propyl]ammonium chloride, octadecyldimethyl[3-(methyldiethoxysilyl)propyl]ammonium chloride, γ-chloropropylmethyldimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, etc. The amount of silane coupling agent added in the chemical conversion treatment agent for forming the chemical conversion treatment film layer 20 can be set to 2 to 80 g / L, for example. When the amount of silane coupling agent added is less than 2 g / L, the adhesion to the plated surface is insufficient, and there is a possibility that the processing adhesion of the film is reduced. On the other hand, when the amount of the silane coupling agent added exceeds 80 g / L, the cohesive force of the chemical conversion coating layer 20 is insufficient, and there is a possibility that the processing adhesion with the coating is reduced.The silane coupling agents listed above may be used alone or in combination of two or more.

[0069] [Silicon dioxide]

[0070] As silica, for example, commercially available silica gels such as "Snowtex N", "Snowtex C", "Snowtex UP", "Snowtex PS" manufactured by Nissan Chemical Co., Ltd., "Adelite AT-20Q" manufactured by ADEKA Co., Ltd., or powdered silica such as Aerosil #300 manufactured by Nippon Aerosil Co., Ltd., or silica equivalent to these commercially available silicas can be used. The silica can be appropriately selected according to the desired performance of the pre-coated plated steel sheet. The amount of silica added in the chemical conversion treatment agent used to form the chemical conversion treatment coating layer 20 is preferably 1 to 40 g / L, for example. When the amount of silica added is less than 1 g / L, there is a possibility that the processing adhesion of the coating is reduced, and when the amount of silica added exceeds 40 g / L, the effects of processing adhesion and corrosion resistance are likely to be saturated, which is not economical.

[0071] [Phosphoric acid and its salts]

[0072] Phosphoric acid and its salts include, for example, phosphoric acid such as orthophosphoric acid, metaphosphoric acid, pyrophosphoric acid, triphosphoric acid, tetraphosphoric acid and their salts; ammonium salts such as triammonium phosphate and diammonium hydrogen phosphate; phosphonic acid such as aminotri(methylenephosphonic acid), 1-hydroxyethylidene-1,1-diphosphonic acid, ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid) and their salts; organic phosphoric acid such as phytic acid and its salts. It should be noted that, regarding phosphoric acid salts, as salts other than ammonium salts, metal salts with Na, Mg, Al, K, Ca, Mn, Ni, Zn, Fe and the like can be listed. Phosphoric acid and its salts can be used alone or in combination of two or more.

[0073] It should be noted that the content of phosphoric acid and its salts is, for example, preferably 0% by mass or more, and more preferably 1% by mass or more, relative to the solid content of the coating. In addition, the content of phosphoric acid and its salts is, for example, preferably 20% by mass or less, and more preferably 10% by mass or less, relative to the solid content of the coating. When the content of phosphoric acid and its salts exceeds 20% by mass, the coating becomes brittle, and there is a case where the processing followability of the coating during the forming of the pre-coated steel sheet is reduced.

[0074] [Fluoride]

[0075] Examples of the fluoride include ammonium zirconium fluoride, ammonium silicon fluoride, ammonium titanium fluoride, sodium fluoride, potassium fluoride, calcium fluoride, lithium fluoride, titanium hydrofluoride, zirconium hydrofluoride, etc. These fluorides may be used alone or in combination of two or more.

[0076] It should be noted that the content of fluoride is preferably 0% by mass or more, more preferably 1% by mass or more, relative to the solid content of the coating. In addition, the content of fluoride is preferably 20% by mass or less, more preferably 10% by mass or less, relative to the solid content of the coating. When the content of fluoride exceeds 20% by mass, the coating becomes brittle, and there is a case where the processing followability of the coating during the forming of the pre-coated steel sheet is reduced.

[0077] [Vanadium compounds]

[0078] As the vanadium compound, for example, vanadium pentoxide, metavanadic acid, ammonium metavanadate, sodium metavanadate, vanadium trichloride and other pentavalent vanadium compounds are reduced with a reducing agent to divalent to tetravalent vanadium compounds, vanadium trioxide, vanadium dioxide, vanadium oxysulfate, vanadium oxyoxalate, vanadium acetylacetonate, vanadium acetylacetonate, vanadium trichloride, vanadium phosphovanadomolybdic acid, vanadium sulfate, vanadium dichloride, vanadium oxide and the like, etc. The vanadium compound can be used alone or in combination of two or more.

[0079] It should be noted that the content of the vanadium compound is preferably 0% by mass or more, more preferably 1% by mass or more, relative to the solid content of the coating. In addition, the content of the vanadium compound is preferably 20% by mass or less, more preferably 10% by mass or less, relative to the solid content of the coating. When the content of the vanadium compound exceeds 20% by mass, the coating becomes brittle, and there is a case where the processing followability of the coating during the forming of the pre-coated steel sheet decreases.

[0080] [Tannin or tannic acid]

[0081] Tannin or tannic acid can use any of hydrolyzable tannin and condensed tannin. Examples of tannin and tannic acid include witch hazel tannin, gallnut tannin, gallic tannin, terminalia chebula tannin, tannin of sappanwood, tannin of tanning materials, tannin of oak bowl, catechin, etc. The amount of tannin or tannic acid added in the chemical conversion treatment agent used to form the chemical conversion treatment coating layer 20 can be set to 2 to 80 g / L. When the amount of tannin or tannic acid added is less than 2 g / L, the adhesion to the plated surface is insufficient, and there is a possibility that the processing adhesion of the coating is reduced. In addition, when the amount of tannin or tannic acid added exceeds 80 g / L, the cohesive force of the chemical conversion treatment coating is insufficient, and there is a possibility that the processing adhesion to the coating is reduced.

[0082] Furthermore, within a range that does not impair the performance, an acid, an alkali, or the like may be added to the chemical conversion agent for forming the chemical conversion coating layer 20 to adjust the pH.

[0083] After applying the chemical conversion agent containing the above-mentioned various components on one or both sides of the galvanized steel sheet 10, drying is performed to form the chemical conversion coating layer 20. In the pre-coated steel sheet of this embodiment, it is preferred to form a 10 mg / m2 per single side on the Zn-containing coating layer 13. 2 The above chemical conversion coating layer 20. The adhesion amount of the chemical conversion coating layer 20 is more preferably 20 mg / m 2 More preferably, 50 mg / m 2 In addition, in the pre-coated steel sheet of the present embodiment, it is preferable to form a Zn-containing coating layer 13 with a Zn content of 1000 mg / m per single surface. 2 The following chemical conversion coating layer 20. The adhesion amount of the chemical conversion coating layer 20 is more preferably 800 mg / m 2 Below, more preferably 600 mg / m 2 The thickness of the chemical conversion coating layer 20 corresponding to the adhesion amount varies depending on the components contained in the chemical conversion agent, but is generally about 0.01 to 1 μm. The thickness of the chemical conversion coating layer 20 can be measured by direct cross-sectional observation.

[0084] It should be noted that the chemical conversion treatment agent described above can be applied by generally known coating methods such as roller coating, curtain coating, air spraying, airless spraying, dipping, rod coating, brush coating, and the like.

[0085] The applied chemical conversion agent can be cured by a known curing method (eg, hot air sintering device, induction heating (IH) device, near infrared heating device, etc.) or a combination of these curing methods.

[0086] Here, in the case of forming a chemical conversion coating, a chemical conversion agent is usually applied to a substrate (in the case of the present embodiment, a galvanized steel sheet 10), and then cured by heating. However, in order to form a zirconium-enriched state described in detail below near the interface of the Zn-containing coating layer 13 side of the coating layer 30 as in the present embodiment, it is necessary to preheat the galvanized steel sheet 10 from, for example, a room temperature state to a temperature exceeding room temperature when applying the chemical conversion agent. Thus, the reactivity of the zirconium-containing component in the chemical conversion agent with the Zn-containing coating layer 13 can be increased, and after the chemical conversion agent is applied, a highly reactive zirconium-enriched layer is formed between the Zn-containing coating layer 13.

[0087] It is important to set the preheating temperature of the galvanized steel sheet 10 to a temperature higher than room temperature when applying the chemical conversion treatment agent. In addition, it is preferred to determine the preheating temperature according to the temperature of the applied chemical conversion treatment agent. For example, it is preferred to preheat the galvanized steel sheet 10 to a temperature of +5°C or more relative to the temperature of the applied chemical conversion treatment agent, and it is more preferred to preheat the galvanized steel sheet 10 to a temperature of +10°C or more.

[0088] On the other hand, when the preheating temperature of the galvanized steel sheet 10 is too high, there is a possibility that the solidification of the chemical conversion treatment agent is excessively accelerated, the cohesion of the chemical conversion treatment film is insufficient, and the processing adhesion of the film is reduced. Therefore, the preheating temperature of the galvanized steel sheet 10 is preferably below +60°C relative to the temperature of the applied chemical conversion treatment agent, and more preferably below +50°C.

[0089] In addition, in order to keep the applied chemical conversion agent as a chemical conversion coating on the galvanized steel sheet, it is necessary to heat the chemical conversion agent after applying it (i.e., heat the chemical conversion agent to solidify it). Here, when the plate temperature of the galvanized steel sheet 10 is too high, there is a possibility that the solidification of the chemical conversion agent is excessively accelerated, the cohesion of the chemical conversion coating is insufficient, and the processing adhesion of the coating is reduced. In addition, when the chemical conversion agent is over-solidified, it will hinder the thermal diffusion of zirconium to the coating layer 30 formed next, and the enriched state of zirconium described in detail below cannot be achieved.

[0090] From the above perspectives, the plate temperature (reaching plate temperature) of the galvanized steel sheet 10 after the chemical conversion treatment agent is applied is preferably determined according to the temperature of the applied chemical conversion treatment agent. More specifically, the plate temperature (reaching plate temperature) of the galvanized steel sheet 10 after the chemical conversion treatment agent is applied is preferably +20°C or more, and more preferably +25°C or more, relative to the temperature of the applied chemical conversion treatment agent (the temperature of the chemical conversion treatment agent when the application starts). In addition, the plate temperature (reaching plate temperature) of the galvanized steel sheet 10 after the chemical conversion treatment agent is applied is preferably +80°C or less, and more preferably +70°C or less, relative to the temperature of the applied chemical conversion treatment agent (the temperature of the chemical conversion treatment agent when the application starts).

[0091] Note that, as long as the plate temperature is within the above range, the heating time is not particularly limited, and any time required to appropriately vaporize the solvent contained in the chemical conversion treatment agent may be ensured.

[0092] The chemical conversion coating layer 20 according to the present embodiment has been described above.

[0093] <About coating layer 30>

[0094] The coating layer 30 is a layer located on the chemical conversion coating layer 20, and as described in detail below, it is a high-thickness coating having an average thickness of 3 μm or more. Figure 1A and Figure 1B As shown schematically, the coating layer 30 contains resin particles 303 and a binder resin 301 as a film-forming component. Since the coating layer 30 contains the resin particles 303, the toughness and ductility of the resin particles 303 can reduce the impact applied to the coating layer 30, thereby improving the damage resistance (especially resistance to scratches) of the coating layer 30. In addition, even if damage occurs on the coating layer 30, it can prevent the damage from reaching the Zn-containing coating layer 13, and the corrosion resistance of the pre-coated steel sheet 1 can be maintained.

[0095] In the pre-coated steel sheet 1 of the present embodiment, the average thickness of the coating layer 30 ( Figure 1A and Figure 1B The thickness d c ) is 3 μm or more. When the average thickness of the coating layer 30 is less than 3 μm, the color tone of the galvanized steel sheet 10 (more specifically, the color tone of the Zn-containing coating layer 13) as the base material may be visible through. The average thickness of the coating layer 30 is preferably 4 μm or more, and more preferably 5 μm or more.

[0096] On the other hand, the average thickness of the coating layer 30 is 10 μm or less. When the average thickness of the coating layer 30 exceeds 10 μm, the cost increases, and coating defects such as wrinkles may occur, and there is a possibility that it is difficult to obtain a stable appearance. In addition, when the average thickness of the coating layer 30 exceeds 10 μm, the coating layer 30 is too thick and the adhesion of the coating layer decreases. The average thickness of the coating layer 30 is preferably 9 μm or less, and more preferably 8 μm or less.

[0097] It should be noted that the average thickness of the coating layer 30 can be measured by direct observation from a cross section. Specifically, the pre-coated steel plate is buried in a room temperature drying epoxy resin so that its cross section can be observed, and its buried surface is mechanically polished, and further finished to a mirror surface state, and then observed by SEM (Scanning Electron Microscope). At this time, the field of view width of the SEM observation is, for example, set to be able to observe a width of 60 μm in a direction perpendicular to the thickness direction. The thickness is measured at any multiple locations (for example, 10 locations), and the average value of the multiple thicknesses obtained is used as the thickness of the coating layer 30.

[0098] In addition, the film thickness can be measured by glow discharge optical emission spectroscopy (GD-OES) to measure the depth curve from the surface side of the coating layer of the pre-coated steel plate to the steel plate side. By checking the sputtering time corresponding to the curve of the coating layer 30 and the thickness of the coating layer obtained from the SEM observation of the above-mentioned cross-section, the thickness of the coating layer per unit sputtering time can be converted.

[0099] It should be noted that, in the depth curve obtained by the glow discharge emission spectrometry, the approximate position of the interface on the Zn-containing plating layer 13 side of the coating layer 30 can be determined as follows. That is, in the depth curve, the position where the intensity of a specific element (e.g., Zn) contained in the Zn-containing plating layer 13 starts to decrease from the peak value in the Zn-containing plating layer 13 and is halved can be determined as the position of the interface on the Zn-containing plating layer 13 side of the coating layer 30. Here, when determining the position in the depth curve as described above, the depth curve is obtained at multiple positions (e.g., 10 locations) of the Zn-containing plating layer 13 to be concerned, and the position of the interface on the Zn-containing plating layer 13 side of the coating layer 30 can be determined based on the average value of the measurement results of the multiple positions obtained.

[0100] 《Binder Resin 301》

[0101] As long as the binder resin 301 as a film-forming component in the coating layer 30 of the present embodiment functions as a binder for the resin particles 303, any raw material can be used. However, from the perspective of simplicity and cost of manufacturing, various organic resins are preferably used. As such a binder resin 301, for example, acrylic resins, polyester resins, polyurethane resins, fluorine resins, etc. can be listed. In addition, in the coating layer 30 of the present embodiment, as the binder resin 301, it is preferred to select a resin of the same type as the resin particles 303. As a result, the affinity between the binder resin 301 and the resin particles 303 is improved, and the adhesion of the coating layer 30 can be further improved.

[0102] In addition, the binder resin 301 of the present embodiment is preferably an organic resin having a glass transition temperature Tg of 30° C. or higher. By using a resin having such a glass transition temperature Tg as the binder resin 301, the coating layer 30 has a more appropriate hardness, and the damage resistance (especially resistance to scratches) of the pre-coated steel sheet 1 can be further improved.

[0103] The glass transition temperature Tg of the binder resin 301 is preferably 35°C or higher, more preferably 40°C or higher. On the other hand, the upper limit of the glass transition temperature Tg is not particularly specified. However, when the glass transition temperature Tg of the binder resin 301 exceeds 70°C, the processability may be reduced. Therefore, the glass transition temperature Tg of the binder resin 301 is preferably 70°C or lower.

[0104] It should be noted that the glass transition temperature Tg can be determined, for example, by the following methods: a method in which a certain temperature change is caused by puncturing the coating as the object of measurement from the surface toward the thickness direction of the coating by TMA (Thermomechanical Analysis), and the thermal expansion change of the object of measurement is measured; a method in which a certain temperature change is caused by applying periodic deformation to the coating as the object of measurement peeled off from the substrate by DMA (Dynamic Mechanical Analysis), and the viscoelasticity is analyzed.

[0105] 《Resin Particles 303》

[0106] The resin particles 303 in the coating layer 30 of the present embodiment are resin particles made of organic resin as raw materials. As mentioned above, the toughness and ductility of the resin particles 303 can mitigate the impact applied to the coating layer 30, thereby further improving the damage resistance of the pre-coated steel sheet 1. As the resin particles, acrylic resin particles, polyester resin particles, polyurethane resin particles, fluorine resin particles, silicone resin particles, polyolefin resin particles, etc. can be listed. Among these resins, acrylic resin particles are more preferably used as the resin particles 303. In addition, as described below, the coating layer 30 can further contain a coloring pigment, and the coloring pigment itself can function as the above-mentioned resin particles 303.

[0107] It should be noted that it is conceivable to use inorganic particles composed of an inorganic compound represented by silica or ceramics instead of the resin particles 303. However, since inorganic particles are relatively brittle particles, the effects obtained by using the resin particles 303 described above cannot be obtained.

[0108] In the coating layer 30 of the present embodiment, the content of the resin particles 303 is preferably 5% by mass or more relative to the total content of the binder resin 301 and the resin particles 303. This can further improve the damage resistance. The content of the resin particles 303 in the coating layer 30 is more preferably 10% by mass or more, and more preferably 11% by mass or more. On the other hand, the content of the resin particles 303 is 50% by mass or less relative to the total content of the binder resin 301 and the resin particles 303. This can further improve the damage resistance. When the content of the resin particles 303 exceeds 50% by mass, the ratio of the binder resin in the coating layer 30 decreases, the barrier properties of the coating decrease, and it is difficult to show the desired corrosion resistance. The content of the resin particles 303 in the coating layer 30 is more preferably 45% by mass or less, and more preferably 15% by mass or less.

[0109] In the coating layer 30 of the present embodiment, the average particle size of the resin particles 303 is preferably in the range of 1.5 to 15.0 μm. The resin particles 303 have the above-mentioned average particle size, which can further improve the damage resistance of the pre-coated steel sheet. The average particle size of the resin particles 303 is more preferably 3.0 μm or more, and more preferably 5.0 μm or more. In addition, the average particle size of the resin particles 303 is more preferably 10.0 μm or less, and more preferably 8.0 μm or less.

[0110] Here, the average particle size of the resin particles 303 can be measured by direct observation from a cross section. Specifically, a pre-coated steel plate is buried in a room temperature drying type epoxy resin so that its cross section can be observed, and after mechanically grinding its buried surface, it is observed by SEM (scanning electron microscope). At this time, the average value of the multiple particle sizes obtained by measuring the particle sizes of the resin particles 303 observed at any multiple positions (for example, 10 positions) can be used as the average particle size of the resin particles 303.

[0111] ◇Average area ratio of the resin particles 303 in the cross section of the coating layer 30

[0112] Next, refer to Figure 2 The average area ratio of the resin particles 303 in the cross section of the coating layer 30 according to the present embodiment will be described. Figure 2 This is an explanatory diagram for explaining the coating layer 30 in the precoated steel sheet 1 of the present embodiment, and schematically shows a cross section of the coating layer 30 of the present embodiment cut along the thickness direction.

[0113] In the coating layer 30 of the present embodiment, the SEM cross-sectional observation is performed to observe the coating layer 30 cut along the thickness direction. Figure 2 In this case, the cross section of the coating layer 30 is shown as an example. Figure 2In the region of 60 μm in length in the direction perpendicular to the thickness direction as shown (more specifically, as shown in Figure 2 The area shown is d c × 60 μm), the average area ratio of the resin particles 303 in the region is 5% or more and 30% or less.

[0114] When the average area ratio of the resin particles 303 is less than 5%, the ratio of the resin particles 303 in the coating layer 30 is too low, and the desired scratch resistance and corrosion resistance as described above cannot be achieved. By setting the average area ratio of the resin particles 303 to 5% or more, the desired scratch resistance and corrosion resistance can be achieved. The average area ratio of the resin particles 303 is preferably 8% or more, and more preferably 11% or more.

[0115] On the other hand, when the average area ratio of the resin particles 303 exceeds 30%, the existence ratio of the resin particles 303 in the coating layer 30 is too high. As a result, although the desired damage resistance can be achieved, it is impossible to achieve both the desired damage resistance and the corrosion resistance. By setting the average area ratio of the resin particles 303 to 30% or less, the desired damage resistance and corrosion resistance can be achieved. The average area ratio of the resin particles 303 is preferably 25% or less, and more preferably 20% or less.

[0116] In addition, in the coating layer 30 of the present embodiment, it is more preferred that the average particle size of the resin particles 303 is in the range of 3.0 to 10.0 μm, the content of the resin particles 30 in the coating layer 30 is 5 to 15% by mass relative to the total content of the binder resin 301 and the resin particles 303, and the average thickness of the coating layer 30 is in the range of 4 to 8 μm. In the coating layer 30 of the present embodiment, by satisfying the above conditions, a more preferred dispersion state of the resin particles 303 is achieved, thereby achieving a more preferred average area ratio of the resin particles 303.

[0117] Here, the average area ratio of the resin particles 303 can be measured by direct observation from the cross section. Specifically, the precoated steel plate 1 is buried in a room temperature drying type epoxy resin so that its cross section can be observed. After the buried surface is mechanically polished and further finished to a mirror surface state, it is observed by SEM (scanning electron microscope). When observing the cross section formed by cutting the coating layer at any position along the thickness direction, a region with a length of 60 μm in a direction orthogonal to the thickness direction is determined, and the area of ​​the coating layer 30 and the total area of ​​the resin particles 303 in the region are measured. By dividing the total area of ​​the obtained resin particles 303 by the area of ​​the coating layer 30, the area ratio of the resin particles 303 at the observation position can be calculated. This measurement is performed at any multiple locations (for example, 10 locations), and the average value of the multiple area ratios obtained based on the number of measurement locations is calculated. The average value thus obtained is used as the average area ratio of the resin particles 303.

[0118] ◇Zirconium distribution in the coating layer 30

[0119] In the pre-coated steel sheet 1 of the present embodiment, as described below, the coating layer 30 is formed by applying a coating material for forming the coating layer 30 on the surface of the galvanized steel sheet 10 on which the chemical conversion coating layer 20 is formed, and then curing and drying the coating material. In the curing and drying process, the coating material is sintered at a predetermined temperature. Due to the heat applied in the curing and drying process, the components contained in the Zn-containing plating layer 13, the components contained in the chemical conversion coating layer 20, and the components contained in the coating material that becomes the coating layer 30 are mutually thermally diffused, so that the zirconium element from the chemical conversion coating layer 20 exists in the coating layer 30. In particular, as described above, when the chemical conversion coating layer 20 is formed, a highly reactive zirconium-rich layer can be formed by preheating and heating under specific conditions. As a result, a specific zirconium distribution state is achieved in the pre-coated steel sheet 1 through the curing and drying process.

[0120] In this embodiment, attention is paid to the zirconium distribution state in the coating layer 30 as described above. Figure 3 The distribution state of zirconium in the coating layer 30 of the present embodiment will be described. Figure 3 This is an explanatory diagram for explaining the coating layer of the precoated steel sheet of the present embodiment, and schematically shows a cross section of the coating layer 30 of the present embodiment when it is cut along the thickness direction. It should be noted that for convenience, Figure 3 In the figure, the distinction between the binder resin 301 and the resin particles 303 in the coating layer 30 is omitted.

[0121] In the present embodiment, when determining the zirconium distribution state in the coating layer 30 , depth profile measurement using glow discharge optical emission spectroscopy (GD-OES) was performed.

[0122] Here, in the depth profile measurement, first, the sample is cut into the required measurement size (e.g., 50 mm). Then, for the obtained measurement sample, the zirconium element is measured under the following measurement conditions. A glow discharge emission surface analyzer (e.g., Marcus type high-frequency glow discharge emission surface analyzer GD-Profiler2 manufactured by HORIBA Jobin Yvon Co., Ltd.) is used, and the measurement is performed under the conditions of gas replacement time of 30 seconds, pre-sputtering time of 30 seconds, pressure of 600 Pa, and output of 35 W until the spectrum of iron from the base steel is detected as the intensity.

[0123] By performing the measurement as described above, it is possible to determine the distribution state of the zirconium element along the thickness direction of the coating layer 30. Based on the measurement results of the obtained depth curve, the depth position (or sputtering time) of the coating layer 30 is used as the horizontal axis, and the luminescence intensity calculated based on the obtained measurement results is used as the vertical axis, so that the depth curve related to zirconium in GD-OES can be visualized.

[0124] In the present embodiment, in the depth curve related to zirconium obtained as described above, the position where the luminescence intensity reaches the maximum (the peak position when the depth curve is macroscopically observed) is defined as the interface on the Zn-containing plating layer 13 side of the coating layer 30 (for example, with Figure 3 The luminescence intensity at this position is set to the interface of the Zn-containing plating layer 13 side of the coating layer 30 ( Figure 3 The intensity of zirconium at position A in the GD-OES. It should be noted that, in GD-OES, due to the characteristics of the measurement method, the luminescence intensity value sometimes fluctuates. Therefore, in this embodiment, the maximum value of the luminescence intensity calculated based on the depth curve is treated as the intensity of zirconium.

[0125] In the present embodiment, in the depth curve related to zirconium obtained as described above, in the range of 1 μm or more and 2 μm or less in the thickness direction of the coating layer 30 from the surface of the coating layer 30 ( Figure 3 In the range from position B to position C in the above-mentioned GD-OES, the average value of the luminous intensity in the corresponding range (hereinafter referred to as "average intensity") is calculated. On this basis, the obtained average intensity is used as a reference for studying the above-mentioned "zirconium intensity at the interface of the Zn-containing coating layer 13 side of the coating layer 30". It should be noted that in the above-mentioned measurement by GD-OES, the measurement is carried out at multiple locations (for example, 10 locations) of the coating layer 30 of interest, and the average value of the measurement results of the multiple locations is used as the above-mentioned average intensity.

[0126] In the coating layer 30 of the present embodiment, the zirconium strength at the interface on the Zn-containing coating layer 13 side of the coating layer 30 obtained as described above is 1.05 times or more and 3.00 times or less relative to the average strength of zirconium in the range of 1 μm or more and 2 μm or less in the thickness direction of the coating layer 30 from the surface of the coating layer 30.

[0127] The fact that the strength ratio is 1.05 times or more and 3.00 times or less suggests that in the coating layer 30 of the present embodiment, zirconium is enriched in the interface portion on the Zn-containing plating layer 13 side of the coating layer 30. In the pre-coated steel sheet 1 of the present embodiment, zirconium is in such an enriched state, which contributes to the improvement of the adhesion of the coating layer 30. Thus, even in the case where the average thickness of the coating layer 30 is 3 μm or more and 10 μm or less, which is a relatively thick film thickness, the coating film adhesion can be further improved.

[0128] When the strength ratio is less than 1.05 times, the zirconium enrichment state of the coating layer 30 is insufficient, and the above-mentioned coating film adhesion improvement effect cannot be obtained. The strength ratio is preferably 1.07 times or more, and more preferably 1.10 times or more.

[0129] On the other hand, if the strength ratio exceeds 3.00 times, the cohesive force of the chemical conversion coating layer is insufficient, and the processing adhesion of the coating layer 30 may decrease, which is not preferred. The strength ratio is preferably 2.50 times or less, and more preferably 2.00 times or less.

[0130] ◇Other components of the coating layer 30

[0131] The coating layer 30 of the present embodiment may further contain at least any one of a cross-linking agent and a coloring pigment in addition to the above-mentioned components.

[0132] By further including a crosslinking agent in the coating layer 30 of the present embodiment, the barrier property of the coating layer 30 itself can be further improved, thereby further improving the damage resistance and corrosion resistance of the pre-coated steel sheet 1. In particular, by including at least one of a melamine resin or an isocyanate resin as a crosslinking agent in the coating layer 30, the damage resistance and corrosion resistance of the pre-coated steel sheet 1 can be further improved. The content of the crosslinking agent is preferably set to about 5 to 40% by mass, for example.

[0133] Furthermore, since the coating layer 30 of the present embodiment further contains a coloring pigment, the coating layer 30 can be set to a desired color tone, and the appearance of the pre-coated steel sheet 1 can be further improved.

[0134] It should be noted that the coloring pigment contained in the coating layer 30 is not particularly limited, and various known pigments can be appropriately used according to the color tone required for the coating layer 30. Examples of such coloring pigments include aluminum pigments, carbon black, and TiO2. In addition, the content thereof can be appropriately set, for example, to about 3 to 60% by mass.

[0135] Furthermore, within the range not impairing the above effects, the coating layer 30 of the present embodiment may further contain anti-rust pigments, surface-modified metal powder or glass powder, dispersants, leveling agents, wax, additives such as aggregates, diluent solvents, etc. as needed.

[0136] Here, when a rust-proof pigment is contained, the content thereof is preferably, for example, 1 to 15% by mass. In addition, various known rust-proof pigments can be used as the rust-proof pigment to be used.

[0137] The coating layer 30 can be formed by applying a coating composition containing the components constituting the coating layer 30 described above onto the surface of the galvanized steel sheet 10 having the chemical conversion coating layer 20, and then sintering the coating composition at a temperature of 150°C or higher and less than 300°C to solidify and dry the coating layer. When the sintering temperature is less than 150°C, the sintering and solidification is insufficient, and the corrosion resistance and damage resistance of the coating layer may be reduced. In addition, zirconium is difficult to fully diffuse, and the above-mentioned specific zirconium distribution state cannot be achieved. On the other hand, when the sintering temperature is 300°C or higher, in addition to the possibility of thermal degradation of the resin component or reduced processability, zirconium diffuses excessively, and as a result, the above-mentioned specific zirconium distribution state cannot be achieved.

[0138] The heating time is not particularly limited as long as the heating temperature is within the above range, and any time required for appropriately evaporating the solvent contained in the coating composition can be appropriately ensured.

[0139] It should be noted that the coating composition described above can be applied by generally known coating methods, such as roller coating, curtain coating, air spraying, airless spraying, dipping, rod coating, brush coating, and the like.

[0140] ◇ Regarding the hardness of the coating layer 30

[0141] The Vickers hardness of the coating layer 30 measured at a depth of indentation from the surface layer to three-quarters of the coating thickness (the size of the test load that can achieve the desired indentation depth is set according to the hardness of the coating layer 30) is preferably 10 to 70 Hv. The Vickers hardness is measured using a universal hardness tester (manufactured by FISCHER INSTRUMENTS Co., Ltd.). Under the above-mentioned indentation depth conditions, the hardness is measured from the coating surface at any 10 locations, whether where the resin particles 303 are present or not, and the average value of the 10 measured values ​​is calculated. The coating layer 30 can further improve damage resistance by having the above-mentioned Vickers hardness. The above-mentioned Vickers hardness shown in the coating layer 30 is more preferably 15 to 65 Hv.

[0142] Above, reference Figure 1A to Figure 3 The precoated steel sheet according to the present embodiment has been described in detail.

[0143] It should be noted that, although the above embodiment focuses on the case where a galvanized steel sheet is used as the base material of the pre-coated steel sheet, the present invention described above is also applicable to various metal sheets other than steel sheets, such as aluminum sheets, zinc sheets, stainless steel sheets, and titanium sheets. That is, the chemical conversion coating layer 20 and the coating layer 30 may be provided on the surface of various metal sheets other than steel sheets.

[0144] Example

[0145] The pre-coated steel sheet of the present invention will be described in detail below with reference to examples and comparative examples. It should be noted that the following example is only an example of the pre-coated steel sheet of the present invention, and the pre-coated steel sheet of the present invention is not limited to the following example.

[0146] (1) Galvanized steel sheet

[0147] As the original plate of the pre-coated steel plate, six types of galvanized steel plates A1 to A6 shown in Table 1 below (all commercially available) were used. The coating adhesion amount in the table is the coating adhesion amount on each single side. The Zn-containing coating layer of the following galvanized steel plate was sprayed with a commercially available sodium orthosilicate alkaline cleaning liquid for 5 seconds, washed with water, and dried.

[0148] [Table 1]

[0149] Table 1

[0150] type Galvanized steel sheet (% indicates mass %) A1 <![CDATA[Hot-dip Zn-11%Al-3%Mg-0.2%Si steel sheet (coating attachment amount 135 g / m on one side) 2 )]]> A2 <![CDATA[Hot-dip galvanized steel sheet (coating adhesion amount: 135 g / m on one side) 2 )]]> A3 <![CDATA[Hot-dip Zn-6%Al-3%Mg steel sheet (coating attachment amount 90 g / m on one side) 2 )]]> A4 <![CDATA[Hot-dip Zn-55%Al-2%Mg-1.6%Si steel sheet (coating adhesion amount: 75 g / m on one side) 2 )]]> A5 <![CDATA[Hot-dip Zn-55%Al-1.6%Si steel sheet (coating adhesion amount 75 g / m on one side) 2 )]]> A6 <![CDATA[Alloyed hot-dip galvanized steel sheet (coating adhesion amount on one side: 50 g / m 2 )]]>

[0151] (2) Chemical conversion treatment coating layer

[0152] A chromate-free chemical conversion treatment agent containing zirconium (a chemical conversion treatment agent composed of ammonium zirconium carbonate, silane coupling agent, phosphoric acid compound, vanadium compound, epoxy resin, etc.) or a chromate-free chemical conversion treatment agent not containing zirconium (a chemical conversion treatment agent composed of tannic acid, silane coupling agent, silica particles, polyester resin, etc.) was prepared. After the galvanized steel sheet was preheated to a temperature exceeding room temperature under the preheating conditions shown in Table 7-1 and Table 7-2 below, the galvanized steel sheet was coated with 100 mg / m2 of the coating per single surface. 2 These chemical conversion treatment agents were applied in a manner of . Then, the chemical conversion treatment agents were dried and cured at the heating temperatures shown in the following Tables 7-1 and 7-2 to form a chemical conversion treatment coating layer.

[0153] It should be noted that in the following Tables 7-1 and 7-2, the preheating temperature of the galvanized steel sheet and the plate temperature after coating are shown as relative temperatures based on the temperature of the chemical conversion treatment agent, and the symbol "+" is omitted. It should be noted that for Example No. 42, since preheating above room temperature was not performed, "-" is recorded in the preheating temperature and plate temperature columns.

[0154] (3) Preparation of coating composition for forming coating layer

[0155] A coating composition used for forming a coating layer is prepared. For a binder resin that functions as a film-forming component, a resin equivalent to the resin shown in the following Table 2 is prepared. For each resin solution, as a cross-linking agent, a cross-linking agent equivalent to the cross-linking agent shown in the following Table 3 is prepared. Furthermore, as resin particles, resin particles equivalent to the resin particles shown in the following Table 4 are prepared. In addition, as a coloring pigment, a coloring pigment equivalent to titanium oxide and carbon black (CB) shown in the following Table 5 is prepared. In addition, as an anti-rust pigment, an anti-rust pigment equivalent to the anti-rust pigment shown in the following Table 6 is prepared. These coating compositions are mixed so as to have the contents shown in the following Tables 7-1 and 7-2. It should be noted that the remainder of the contents recorded in Tables 7-1 and 7-2 is the content of the binder resin.

[0156] [Table 2]

[0157] Table 2

[0158] type Binder resin B1 Mitsui Chemicals, Inc. "ALMATEX E208" (water-based acrylic resin) B2 Mitsui Chemicals, Inc. "ALMATEX E255" (water-based acrylic resin) B3 "Vylonal MD-1480" (water-based polyester resin) manufactured by Toyobo Co., Ltd. B4 "SUPER FLEX 150" (water-based polyurethane resin) manufactured by Daiichi Kogyo Seiyaku Co., Ltd.

[0159] [Table 3]

[0160] Table 3

[0161] type Crosslinking agent C1 "NIKALAC MX-035" (melamine resin for water-based paint) manufactured by Sanwa Chemical Co., Ltd. C2 "Elastron BN-69" (blocked isocyanate) manufactured by Daiichi Kogyo Seiyaku Co., Ltd. C3 Mix B1 and B2 in a ratio of 1:1 C4 Shin-Etsu Chemical Co., Ltd. "KBM-603" (silane coupling agent)

[0162] [Table 4]

[0163] Table 4

[0164] type Resin particles D1 Sekisui Chemical Co., Ltd. "SSX-101" (acrylic resin particles, average particle size 1 μm) D2 "MZ-5HN" manufactured by Soken Chemical Co., Ltd. (acrylic resin particles, average particle size 5 μm) D3 "BM 30X-8" manufactured by Sekisui Chemical Co., Ltd. (acrylic resin particles, average particle size 8 μm) D4 "MZ-12H" manufactured by Soken Chemical Co., Ltd. (acrylic resin particles, average particle size 12 μm) D5 "HSP-1000" manufactured by Toagosei Co., Ltd. (silicon dioxide particles, average particle size 1 μm) D6 Mitsui Chemicals, Inc. "CHEMIPEARL W800" (polyolefin resin particles, average particle size 8 μm) D7 Negami Industry Co., Ltd. "P-800T" (polyurethane resin particles, average particle size 6 μm)

[0165] [Table 5]

[0166] Table 5

[0167] type Coloring Pigments E1 Titanium oxide "TIPAQUER-980" manufactured by Ishihara Sangyo Co., Ltd. E2 Carbon black "MCF#950" manufactured by Mitsubishi Chemical Corporation

[0168] [Table 6]

[0169] Table 6

[0170] type Rust inhibitor F1 Condensed aluminum phosphate "K-WHITE#105" manufactured by TAYCA Corporation Average particle size 1.6 μm

[0171] The coating composition for forming a coating layer prepared as described above is applied to the surface of a galvanized steel sheet provided with a chemical conversion treatment coating layer so that the average thickness after drying is the value described in Table 7-1 and Table 7-2, and then cured and dried by heating at a temperature above 150°C and below 300°C.

[0172] [Table 7-1]

[0173]

[0174] [Table 7-2]

[0175]

[0176] For each of the obtained pre-coated steel sheets, depth profile measurement and peak intensity ratio calculation by GD-OES were performed according to the method described above, and the average area ratio of the resin particles was measured. The obtained results are summarized in the above Tables 7-1 and 7-2.

[0177] In addition, the color tone transmittance was evaluated using each coating composition used and each pre-coated steel plate obtained, and the ethanol friction resistance, scratch resistance and processing adhesion of each pre-coated steel plate obtained were evaluated. For each evaluation, the evaluation method and evaluation criteria are as follows. The results are summarized in the following Table 8.

[0178] <Color tone transmittance>

[0179] The color transmittance was evaluated using a colorimeter (CR-400 manufactured by Konica Minolta Co., Ltd.) according to the following criteria. For each of the prepared pre-coated steel plates, steel plates with different color layer thicknesses (more specifically, steel plates coated with the prepared coating composition with a sufficiently thick film thickness) were prepared in advance, and the color tone (L*, a*, b*) was measured as a benchmark. In addition, the color tone (L*, a*, b*) of each of the pre-coated steel plates shown in Table 7-1 and Table 7-2 was also measured in the same manner, and the color difference ΔE was calculated. The obtained color difference ΔE was evaluated according to the following evaluation criteria, and a score of 2 or more was considered acceptable.

[0180] [Evaluation criteria]

[0181] Rating 3: ΔE is 3 or less

[0182] 2: ΔE is more than 3 and less than 5

[0183] 1: ΔE exceeds 5

[0184] <Ethanol friction resistance>

[0185] For each of the obtained pre-coated steel sheets, the ethanol friction resistance was evaluated according to the following criteria. The surface of the obtained pre-coated steel sheet was rubbed back and forth 20 times with a gauze impregnated with ethanol under a load of 1 kgf (1 kgf is about 9.8 N). The appearance of the coating film after rubbing was visually evaluated, and the exposed area ratio of the plating was calculated and evaluated according to the following evaluation criteria. A score of 3 or above was considered acceptable.

[0186] [Evaluation criteria]

[0187] Rating 5: No appearance change

[0188] 4: Although residual traces were observed, exposure of the base plating was not observed

[0189] 3: Residual traces are confirmed, the coating is partially peeled off, and the plating is exposed by more than 1% and less than 10%

[0190] 2: Residual traces are confirmed, the coating is partially peeled off, and the plating is exposed by more than 10% and less than 50%

[0191] 1: Residual traces are confirmed, the coating is partially peeled off, and the plating is exposed by more than 50%

[0192] <Scratch resistance>

[0193] For each of the obtained pre-coated steel sheets, the scratch resistance was evaluated by a coin scratch test according to the following criteria. A coin was made to contact the obtained pre-coated steel sheet at an angle of 45 degrees and scratched with a load of 500 g. Visual evaluation was performed according to the following criteria. A score of 3 was considered acceptable.

[0194] [Evaluation criteria]

[0195] Score 3: No peeling of the coating film was observed.

[0196] 2: Partial peeling of the coating film was confirmed.

[0197] 1: The coating film is completely peeled off.

[0198] <Processing Adhesion>

[0199] For each of the obtained pre-coated steel sheets, the processing adhesion was evaluated according to the following criteria. Each of the obtained pre-coated steel sheets was bent at 90° within the condition of R1mm in an atmosphere at 20°C, and then a tape peeling test was performed on the outside of the bent portion. The appearance of the tape peeling portion was evaluated according to the following evaluation criteria. A score of 3 was qualified.

[0200] [Evaluation criteria]

[0201] Score 3: No peeling of the coating film was observed.

[0202] 2: Partial peeling of the coating film was confirmed.

[0203] 1: Peeling of the entire coating film was confirmed.

[0204] <Corrosion resistance after scratching>

[0205] For each pre-coated steel plate obtained, a scratch is given using a coin scratch test according to the following criteria. A coin is made to contact the obtained pre-coated steel plate at an angle of 45 degrees, and is scratched with a load of 1000g. Then, a salt spray test (SST) according to JIS Z 2371:2015 is performed for 72 hours. The test material after the test is cleaned and dried, and the maximum white rust width from the scratched part is measured. The maximum single-sided white rust width of the white rust generated on both sides of the scratched part is measured. A 10x magnifying glass is used for observation. Corrosion resistance is evaluated according to the following evaluation criteria. The qualified level is 2 or above.

[0206] [Evaluation criteria]

[0207] Score 4: The maximum width of white rust generated from the scratched portion is less than 0.5 mm on one side.

[0208] 3: The maximum width of white rust generated from the scratched portion is more than 0.5 mm and less than 1.0 mm on one side.

[0209] 2: The maximum width of white rust generated from the scratched portion is more than 1.0 mm on one side and less than 2.0 mm.

[0210] 1: The maximum width of white rust generated from the scratched part exceeds 2.0 mm on one side.

[0211] [Table 8]

[0212] Table 8

[0213]

[0214] As is apparent from Table 8, the precoated steel sheets corresponding to the examples of the present invention have both excellent scratch resistance and coating film adhesion, whereas the precoated steel sheets corresponding to the comparative examples of the present invention have insufficient scratch resistance or coating film adhesion.

[0215] The preferred embodiments of the present invention are described in detail with reference to the attached drawings, but the present invention is not limited to the examples. Obviously, a person with common sense in the technical field to which the present invention belongs can think of various variations or modifications within the scope of the technical ideas recorded in the patent claims, and it can be understood that these also belong to the technical scope of the present invention.

[0216] The embodiments disclosed this time are exemplary and non-restrictive in all aspects. The above embodiments may be omitted, replaced or changed in various forms without departing from the attached patent claims, the technical features belonging to the technical scope of the present invention described later, and the gist thereof. For example, the technical features of the above embodiments may be arbitrarily combined without impairing their effects. In addition, the arbitrary combination can of course obtain the functions and effects of the various technical features involved in the combination, and at the same time, those skilled in the art can obtain other obvious functions and effects based on the description of this specification.

[0217] In addition, the effects described in this specification are only illustrative or exemplary, and not limiting. That is, in addition to or instead of the above effects, those skilled in the art can obtain other obvious effects based on the description of this specification.

[0218] It should be noted that the following technical features also belong to the technical scope of the present invention.

[0219] (1) A pre-coated steel sheet having:

[0220] A Zn-containing coating layer located on the surface of a base steel plate;

[0221] a chemical conversion coating layer located on the Zn-containing coating layer and containing at least zirconium; and

[0222] a coating layer located on the chemical conversion treatment coating layer,

[0223] The coating layer contains at least a binder resin and resin particles.

[0224] The average thickness of the coating layer is 3 μm or more and 10 μm or less.

[0225] The intensity of zirconium at the interface of the coating layer on the Zn-containing plated layer side calculated from a depth curve associated with zirconium distribution of the coating layer obtained by glow discharge emission spectroscopy is 1.05 to 3.00 times the average intensity of zirconium in a range of 1 μm to 2 μm from the surface of the coating layer toward the thickness direction of the coating layer calculated from the depth curve,

[0226] When observing a cross section of the coating layer cut along the thickness direction, in a region having a length of 60 μm in a direction perpendicular to the thickness direction, the average area ratio occupied by the resin particles in the region is 5% to 30%.

[0227] (2) The precoated steel sheet according to (1), wherein the coating layer further contains at least one of a crosslinking agent and a coloring pigment.

[0228] (3) The precoated steel sheet according to (2), wherein the cross-linking agent is at least one of a melamine resin and an isocyanate resin.

[0229] (4) The precoated steel sheet according to any one of (1) to (3), wherein the resin particles are made of the same type of resin as the binder resin.

[0230] (5) The precoated steel sheet according to any one of (1) to (4), wherein the average particle size of the resin particles is within a range of 1.5 to 15.0 μm.

[0231] (6) The precoated steel sheet according to any one of (1) to (5), wherein the average particle size of the resin particles is in the range of 3.0 to 10.0 μm.

[0232] The content of the resin particles in the coating layer is 5 to 15% by mass relative to the total content of the binder resin and the resin particles, and

[0233] The average thickness of the coating layer is in the range of 4 to 8 μm.

[0234] (7) The precoated steel sheet according to any one of (1) to (6), wherein the resin particles are acrylic resin particles.

[0235] Description of Reference Numerals

[0236] 1 Pre-coated steel plate

[0237] 10 Galvanized steel sheet

[0238] 11. Base steel plate

[0239] 13 Zn-containing coating

[0240] 20 Chemical conversion treatment coating layer

[0241] 30 coating layer

[0242] 301 Binder Resin

[0243] 303 Resin Pellets

Claims

1. A pre-coated steel sheet, comprising: A Zn-containing coating layer located on the surface of a base steel plate; a chemical conversion coating layer located on the Zn-containing coating layer and containing at least zirconium; and a coating layer located on the chemical conversion treatment coating layer, The coating layer contains at least a binder resin and resin particles. The average thickness of the coating layer is 3 μm or more and 10 μm or less. The intensity of zirconium at the interface of the coating layer on the Zn-containing plated layer side calculated from a depth curve associated with zirconium distribution of the coating layer obtained by glow discharge emission spectroscopy is 1.05 to 3.00 times the average intensity of zirconium in a range of 1 μm to 2 μm from the surface of the coating layer toward the thickness direction of the coating layer calculated from the depth curve, When observing a cross section of the coating layer cut along the thickness direction, in a region having a length of 60 μm in a direction perpendicular to the thickness direction, the average area ratio occupied by the resin particles in the region is 5% to 30%.

2. The pre-coated steel sheet according to claim 1, wherein: The coating layer further contains at least one of a cross-linking agent and a coloring pigment.

3. The pre-coated steel sheet according to claim 2, wherein: The cross-linking agent is at least one of melamine resin and isocyanate resin.

4. The pre-coated steel sheet according to claim 1 or 2, wherein: The resin particles are made of the same type of resin as the binder resin.

5. The pre-coated steel sheet according to claim 1 or 2, wherein: The average particle size of the resin particles is in the range of 1.5 to 15.0 μm.

6. The pre-coated steel sheet according to claim 1 or 2, wherein: The average particle size of the resin particles is in the range of 3.0 to 10.0 μm. The content of the resin particles in the coating layer is 5 to 15% by mass relative to the total content of the binder resin and the resin particles, and The average thickness of the coating layer is in the range of 4 to 8 μm.

7. The pre-coated steel sheet according to claim 1 or 2, wherein: The resin particles are acrylic resin particles.

Citation Information

Patent Citations

  • Precoated metallic plate for electronic / electrical equipment

    JP2010005545A

  • Method for coating ceramic film on metal, electrolysis solution for use in the method, and ceramic film and metal material

    CN101522957A

  • Coated tool

    JP2009220241A

  • Surface-coated cutting tool with hard coating layer maintaining excellent abrasion resistance and chipping resistance

    JP2013184271A